2012
DOI: 10.4236/jep.2012.311173
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Radioactivity Contents and Associated Risks in Some Soil Used for Agriculture and Building Materials in Cameroon

Abstract: A survey of radioactivity content and associated radiological risks was carried out in various soils used for agriculture and building materials in Cameroon by means of a well-calibrated high-purity germanium detector. Soil samples were collected directly from the agricultural farms and the brick's factories, air-dried at room temperature to a constant mass, crushed, sieved and sealed for at least one month before analysis. The specific activity of 238 U ranged from 5.36 ± 0.39 to 51.28 ± 9. ; The mean result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…However, Vukasinovic et al [30] also found the soil profile with the highest average radionuclide activity concentration contained the lowest sand percentage. This finding was also observed by Al-Sulaiti [31] who indicated that the finest soil grain size had the highest activity concentration of 40 K. Also, the variability of 40 K among regions could be due to the differences in land management, for example, fertilization, plowing practices, geology and geography [32].…”
Section: Distribution Of Natural Radionuclides In the Surface Soilsupporting
confidence: 75%
“…However, Vukasinovic et al [30] also found the soil profile with the highest average radionuclide activity concentration contained the lowest sand percentage. This finding was also observed by Al-Sulaiti [31] who indicated that the finest soil grain size had the highest activity concentration of 40 K. Also, the variability of 40 K among regions could be due to the differences in land management, for example, fertilization, plowing practices, geology and geography [32].…”
Section: Distribution Of Natural Radionuclides In the Surface Soilsupporting
confidence: 75%
“…The radioactivity in soil has been studied in many regions of the world [4][5][6][7][8][9][10][11][12][13]. In India the work on the radioactivity in soil is scattered.…”
Section: Introductionmentioning
confidence: 99%